Is Depression Dialyzable? - Sourabh Sharma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Depression is a common and debilitating comorbidity inpatients with chronic kidney disease (CKD), particularlythose with end-stage kidney disease (ESKD, CKD stage 5).This association stems from a complex interplay ofbiological and psychosocial factors, including theaccumulation of uraemic toxins such as middlemolecules, chronic inflammation, and the psychologicalburden of disease progression. Initiation of dialysis hasbeen observed to alleviate depressive symptoms throughmultiple mechanisms: removal of uraemic toxins,improvement in physical health, and reduction inpsychosocial stressors. This article reviews thepathophysiological underpinnings of depression in CKD,explores the impact of dialysis on depressive symptoms,and evaluates whether depression can be considered a"dialyzable" entity. Keywords: chronic kidney disease, depression, dialysis,middle molecules, uremic toxins, anxiety, ESRD, mentalhealth